Peer Training Using Cognitive Rehearsal to Promote a Culture of Safety in Health Care. Issue 5 (September 2018) - Roberts, Toni; Hanna, Kimberly; Hurley, Shelia; Turpin, Rebecca; Clark, Susan
Abstract : Nursing students need opportunities to prepare for real-world problems that they may encounter as they enter the profession. Incivility and bullying behaviors persist in health care. The purpose of this project was to increase students' awareness of incivility and prepare them to respond to it. Two teaching methods were compared. Results supported that interactive civility training using cognitive rehearsal provided by nursing student peers was as effective as instruction from an expert.